2022
DOI: 10.1002/wsb.1386
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife whodunnit: forensic identification of predators to inform wildlife management and conservation

Abstract: Genetic evidence at predation sites is rapidly improving predator‐prey interaction studies and can provide information beyond field‐based investigations. However, factors contributing to the retention of genetic evidence have received limited investigation in a field setting, and researchers have yet to leverage genetic evidence to improve traditional field investigations. Using data from 61 mortality investigations of mule deer (Odocoileus hemionus), white‐tailed deer (O. virginianus), and elk (Cervus canaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…We therefore recommend the collection of more samples in monsoon followed by summer and winter. We endorse previous suggestions to collect samples promptly to prevent degradation and minimise the influence of scavengers (Ganz et al, 2023; Mumma et al, 2014). Additionally, we strongly recommend collecting multiple sources of samples, including predation samples (such as saliva from fatal wounds and shed hair from the point of kill), at all sites, as these samples aid in differentiation between predators and scavengers, ultimately strengthening confidence assignment in identification.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We therefore recommend the collection of more samples in monsoon followed by summer and winter. We endorse previous suggestions to collect samples promptly to prevent degradation and minimise the influence of scavengers (Ganz et al, 2023; Mumma et al, 2014). Additionally, we strongly recommend collecting multiple sources of samples, including predation samples (such as saliva from fatal wounds and shed hair from the point of kill), at all sites, as these samples aid in differentiation between predators and scavengers, ultimately strengthening confidence assignment in identification.…”
Section: Discussionsupporting
confidence: 76%
“…Genetic methods are more effective in predator identification than field-based methods (Ganz et al, 2023; Mumma et al, 2014). Samples can also be collected from human predation sites where use of conventional methods becomes a challenge and has ethical considerations (Pandey & Sharma, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification from the visual examination of livestock wounds can be ambiguous, as overlap between attack characteristics of different predators makes species discrimination prone to observer bias, especially due to delayed response time, insufficient experience, or if a carcass has been visited by several predator and/or scavenger species [ 24 ]. Genetic analysis, supported by detailed field reports and necropsies, is highly preferred for accurate identification [ 10 , 26 , 61 ]. In the present study, we identified DNA saliva from dog and puma in the calf carcass, but we could not deduce the identity of the initial predator versus a scavenger.…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of using radiotelemetry and temperature loggers is the inability to discern among predator species. To estimate the impact of specific predators in an ecosystem with several predators, other methods would be necessary (e.g., Ganz et al, 2023). Several lines of evidence indicated otter activity and predation on salmon in the two rivers (Box 1), supporting the assumption that tags found on land were evidence of otter kills.…”
Section: Discussionmentioning
confidence: 99%